Aplikasi Sistem Pakar Diagnosa Kerusakan Motor Matic Injeksi Berbasis Web (Studi Kasus: Bengkel Pelangi Motor) - Andika Maulana Putra; Joko Suwarno (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract In the case study at the Pelnagi Motor workshop located on Jl.Raya Serua Cinangka, Bojongsari District, Depok City, there is a problem that there is no automatic system to analyze damage to an injection matic motorbike to ease the work of mechanics or workshop mechanics. This research aims to design a web-based expert system application to help and facilitate the work of a mechanic or workshop mechanic. Researchers use the Prototyping Model as a method of designing systems that are built. And the use of the Forward Chaining method as the brain of the expert system. The system is implemented into a damage detection/diagnosis web application that can help mechanics or mechanics analyze customer vehicle damage and receive repair instructions quickly. Keywords: Injection Matic Motorcyle, Expert System, Forward Chaining